A novel strategy based on a ligand-switchable nanoparticle delivery system for deep tumor penetration. Issue 3 (8th January 2019) - Ding, Yuxun; Liu, Jinjian; Zhang, Yumin; Li, Xue; Ou, Hanlin; Cheng, Tangjian; Ma, Lin; An, Yingli; Liu, Jianfeng; Huang, Fan; Liu, Yang; Shi, Linqi
Abstract : The ligand-switchable nanocarriers (LSNs) concealed CPPs into the bloodstream and expose them upon entering into the tumor sites, and overall improving the therapeutic effect. Abstract : The poor tumor penetration of many nanomedicines severely limits their therapeutic efficiency. Although the combination of cell-penetrating peptides (CPPs) has been reported as a promising strategy to improve the penetration capability of nanoparticles, the nonspecific interactions of CPPs may reduce nanoparticles' circulation time and increase their side effects, making them inapplicable in many in vivo settings. Herein, we report a ligand-switchable strategy to inhibit CPPs' nonspecific interactions in the bloodstream and quickly reactivate their functions when entering into tumor sites. Due to the rapid phase transition of PAE, the CPPs can be completely hidden under the PEG corona in plasma, avoiding direct interaction with the immune cells and normal tissues. Once extravasation from blood vessels occurs, the acidic tumor microenvironment would trigger the exposure of the CPPs, promoting the diffusion of antitumor agents deep into the tumor sites. With this ligand-switchable property, nanocarriers are capable of achieving long durations of circulation, preferential accumulation and efficient tumor penetration simultaneously, giving rise to high antitumor activity and low adverse reactions, and also providing a universal approach to enable in vivo applications of CPPs as well as other nonspecific ligands.